2016
DOI: 10.1159/000446379
|View full text |Cite
|
Sign up to set email alerts
|

NASH Cirrhosis - the New Burden in Liver Transplantation: How Should It Be Managed?

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is a continuously increasing cause of chronic liver disease and a health burden in all populations affected by the obesity and metabolic syndrome pandemic. Cirrhotic alterations or hepatocellular carcinoma developing from NAFLD may require liver transplantation (LTx). Methods: Current literature was screened for data on LTx in the setting of NAFLD. Results: NAFLD-associated LTx is expected to increase in number and relevance during the next decade. NAFLD is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…However, almost one-third of patients who receive liver transplant for NASH will have recurrence of the disease in the transplanted liver in the absence of intense post-transplant lifestyle modifications. 105 , 106 …”
Section: Liver Transplantationmentioning
confidence: 99%
“…However, almost one-third of patients who receive liver transplant for NASH will have recurrence of the disease in the transplanted liver in the absence of intense post-transplant lifestyle modifications. 105 , 106 …”
Section: Liver Transplantationmentioning
confidence: 99%
“…NASH can cause some serious complications, such as liver failure [1], cirrhosis [2,3] and hepatocellular carcinoma [4]. Furthermore, NASH risk is increasing worldwide [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that approximately one-third of the current population in industrialized countries has NAFLD as a consequence of the liver’s involvement in the context of MetS. As mentioned above and according to many authors, it is clear that over the next ten or twenty years, the prevalence of NAFLD will increase due to the epidemic rise in obesity, T2DM, arterial hypertension and the prevalence of MetS, as well as people living longer[ 10 - 13 ]. Consequently, NAFLD-related liver disease is currently the most rapidly increasing indication for LT in the US, and it is anticipated that NAFLD-related liver disease will become the leading indication for LT in the near future[ 14 , 15 ].…”
Section: Nafld Related End-stage Liver Disease and Hcc As Indicationsmentioning
confidence: 99%
“…Similarly, a recently published US study found that HCC as a consequence of NASH is the fastest growing indication for LT. The authors of this study reported that NASH related HCC as an indication for LT had an almost fourfold increase since 2002; on the other hand, HCC that results from HCV, doubled[ 13 , 21 ].…”
Section: Nafld Related End-stage Liver Disease and Hcc As Indicationsmentioning
confidence: 99%